Clinical Impact of Cystatin C/Cathepsin L and Follistatin/Activin A Systems in Breast Cancer Progression: A Preliminary Report. (20th October 2016) - Leto, Gaetano; Incorvaia, Lorena; Flandina, Carla; Ancona, Chiara; Fulfaro, Fabio; Crescimanno, Marilena; Sepporta, Maria Vittoria; Badalamenti, Giuseppe
ABSTRACT: This study was directed to assess the clinical impact of the circulating cathepsin L, cystatin C, activin A, and follistatin in breast cancer patients. The serum concentrations of these molecules were determined by immunoenzymatic assays, and their association with some clinico-pathological parameters of breast cancer progression was evaluated. Our results identified cystatin C and activin A as predictive markers for the presence of breast cancer and bone metastasis, respectively. Therefore, these proteins may have a clinical role as circulating biomarkers in the diagnosis and therapeutic monitoring of breast cancer patients.